2007
DOI: 10.1111/j.1365-2400.2007.00584.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecological traits of fish assemblages from Mediterranean Europe and their responses to human disturbance

Abstract: Mediterranean river systems are characterised by more diverse fish assemblages and regional ecological processes compared with the rest of Europe. A data set from Mediterranean France, Iberia and Greece ( 2000 sites) was used to describe the characteristics of fish assemblages, explore their responses to anthropogenic disturbance and analyse the implications for river quality assessment. There was a southwards decline in species richness per site, but endemicity and proportion of alien species increased. Sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
63
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 27 publications
6
63
0
4
Order By: Relevance
“…Another important aspect in ecological modelling involves the evaluation and interpretation of the results. The presented models were in accordance with the literature due to the fact that the selected input variables, such as water quality, flow regime and the status of riparian forest, are of great importance for the Mediterranean fish populations (Granado-Lorencio, 1996, 2000Bernardo et al, 2003;Ferreira et al, 2007). Both models had three variables in common to predict fish richness: drainage area (DRA), quality index of the riparian forest (QBR) and the biological index for water quality (IBMWP).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Another important aspect in ecological modelling involves the evaluation and interpretation of the results. The presented models were in accordance with the literature due to the fact that the selected input variables, such as water quality, flow regime and the status of riparian forest, are of great importance for the Mediterranean fish populations (Granado-Lorencio, 1996, 2000Bernardo et al, 2003;Ferreira et al, 2007). Both models had three variables in common to predict fish richness: drainage area (DRA), quality index of the riparian forest (QBR) and the biological index for water quality (IBMWP).…”
Section: Discussionsupporting
confidence: 56%
“…Although the two statistical techniques considered different HMU types, one can observe how the spatial distribution and dynamics of mesohabitats can be of great importance for fish conservation (Fausch et al, 2002). According to Bernardo et al (2003) riffles and runs can influence the composition of Mediterranean fish communities; particularly for those dominated by the family Cyprinidae (Granado-Lorencio, 2000;Ferreira et al, 2007), because these mesohabitats can offer good conditions in terms of food availability and shelters. Mean annual flow rate (FMA), the coefficient of variation of mean monthly flow (FIM) along with the channel length without artificial barriers (CWB) were only selected by ANN.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, similar pattern in species diversity was observed. These results are in accordance with numerous previous studies (Godinho et al, 1997(Godinho et al, , 2000Carmona et al, 1999;Pires et al, 1999Pires et al, , 2004Mesquita and Coelho, 2002;Magalhães et al, 2002aMagalhães et al, , 2002bMagalhães et al, , 2007Clavero et al, 2004;Ferreira and Oliveira, 2004;Clavero and Garcia-Berthou, 2006;Mesquita et al, 2006;Ferreira et al, 2007aFerreira et al, , 2007b. In fact, increasing local species richness along the longitudinal stream gradient is a very well known pattern (e.g.…”
Section: Figuresupporting
confidence: 82%
“…The fish grouping obtained in this study was in general consistent with previous patterns observed for the Iberian Peninsula (e.g. Ferreira and Oliveira, 2004;Ferreira et al, 2007a). These results, along with those obtained from the other biological elements considered in the WFD, were used to set the final typology for Portuguese rivers (INAG, 2008a) and constitutes a fundamental tool in planning and managing of water resources.…”
Section: Figuresupporting
confidence: 75%
“…These theoretical studies also stimulated work on applied aspects of trait responses to human-caused stressors (or release from stress after restoration) of organisms such as benthic stream invertebrates Dolédec et al, 1999), stream fish (Ferreira et al, 2007;Schmutz et al, 2007), benthic pond or lake invertebrates (Menetrey et al, 2005;Van Kleef et al, 2006), waterway hydrophytes (Willby, Pygott & Eaton, 2001), lagoon fish, benthic invertebrates, macrophytes and plankton (Mouillot et al, 2006;Pravoni, Da Ponte & Torricelli, 2008), marine benthic invertebrates (Bremner, Frid & Rogers, 2003a;Frid et al, 2008), marine fish (Jennings, Greenstreet & Reynolds, 1999), fluvial floodplain plants, molluscs and insects (Dziock, 2006;Foeckler et al, 2006;Henle et al, 2006) or forest birds (Hausner, Yoccoz & Ims, 2003). These recent assessments of the potential of multiple biological traits to indicate human-caused stressors across a diverse range of organismic groups and ecosystem types indicate perhaps the beginning of a new era in biomonitoring (see also Baird, Rubach & Van den Brink, 2008), the era of using multiple Biological Traits as Indicators (BTIs) of human-caused stressors across ecosystem types.…”
Section: Benign Heterogenous Traitsmentioning
confidence: 99%